Komunikasi Orang Tua dengan Anak dalam Upaya Mengantisipasi Kebebasan Seks di Luar Nikah - Dwi Prijono Soesanto; Muhammad Shaufi (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2019)
One reason to increase efforts to prevent children in sex freedom before marriage is to establish interpersonal communication with children. The reason is that the blurry portraits of Indonesian teenagers are caused by smelling cases of pornography, ranging from free sex, abortion, to HIV / AIDS. One of the causes of this phenomenon is the lack of interpersonal communication between parents and children. The paradigm used is Post-positivism, with a qualitative research approach and descriptive analysis method. The theory used is the theory of the formation of attitudes and behavior by Yvon. Research result; Parents find it difficult to communicate with children, especially openness about the issue of sexual freedom. Some ways that parents do include: Creating a comfortable and interesting communication atmosphere for children, through the style of telling stories about topics that are up to date, etc. Interpersonal communication carried out by parties who have a positive attitude, will greatly support the success of communication. The parties do not have suspicions, suspicions and negative allegations, but rather positive. More than that, parents must also be able to be flexible in terms of positioning. Parents are forbidden to be selfish, just want to be above the child. In communicating privately with children, parents must understand when when as a parent, when as a friend and when as a person who is under the child. Equality in interpersonal communication between parents and children is very important, so that communication can run smoothly, flow without the burden, and can talk about the issue of sexual freedom.